Study of the Structure of MnxFe3-xO4-Poly(m-Aminobenzene Sulfonic Acid) Composites Based on Natural Sand - Andy Choerullah; Sunaryono Sunaryono; Arif Hidayat; Nik Ahmad Nizam Nik Malek (JPSE (Journal of Physical Science and Engineering), 2022)
MnxFe3-xO4-Poly(m-ABS) nanocomposite has been successfully synthesized by in-situ polymerization. In the formation of MnxFe3-xO4-Poly(m-ABS) nanocomposites, FeCl synthesized from iron sand acts as an oxidant and m-aminobenzenesulfonic acid (m-ABS) as a monomer. Structural characterization has been successfully carried out using XRD, FTIR, and SEM. XRD test results show that the MnxFe3-xO4-Poly(m-ABS) nanocomposite has a particle size of about 10.62 nm. The appearance of peaks (111) and (620) with low intensity indicated the presence of poly(m-ABS). This low intensity was probably caused by the amorphous character of polyaniline and its derivatives. The FTIR results show the appearance of asymmetrical and symmetrical S=O strains, S-O, and C-S strains are the main characteristics of poly(m-ABS) which indicate the success of monomer polymerization. The results of the SEM test show that circular shapes dominate the particles with varying sizes with an average size of 42 nm. This result is different from the XRD results because SEM can only measure the surface of the particles, so the resulting size tends to be larger. Based on the study of the structure obtained shows that the MnxFe3-xO4-Poly(m-ABS) nanocomposite has the potential to be applied to energy conversion devices.DOI: 10.17977/um024v7i12022p016